2003
DOI: 10.1152/ajpgi.00152.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sodium current in human intestinal interstitial cells of Cajal

Abstract: Interstitial cells of Cajal (ICC) generate the electrical slow wave required for normal gastrointestinal motility. The ionic conductances expressed in human intestinal ICC are unknown. The aim of this study was to determine expression of a Na+ current in human intestinal ICC and to determine the effects of the Na+ current on the slow wave. Visually identified, freshly dissociated, single ICC were verified by the presence of c-kit mRNA by using single-cell RT-PCR. Standard whole cell currents were recorded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
174
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 38 publications
4
174
0
Order By: Relevance
“…The observation that families with SCN5A-related cardiac channelopathies report much higher incidence of abdominal pain than a control population has led to the hypothesis that sodium channelopathies may be a contributing cause in the pathogenesis of functional bowel disorders (67). The Na v 1.5 voltage-gated sodium channel encoded by SCN5A is expressed in human jejunal epithelial cells and interstitial cells of Cajal (68). In a study of an IBS cohort, one patient with a family history of IBS exhibited a loss-of-function G298S missense mutation on a background of a common H558R polymorphism in SCN5A (69).…”
Section: Visceral Painmentioning
confidence: 99%
“…The observation that families with SCN5A-related cardiac channelopathies report much higher incidence of abdominal pain than a control population has led to the hypothesis that sodium channelopathies may be a contributing cause in the pathogenesis of functional bowel disorders (67). The Na v 1.5 voltage-gated sodium channel encoded by SCN5A is expressed in human jejunal epithelial cells and interstitial cells of Cajal (68). In a study of an IBS cohort, one patient with a family history of IBS exhibited a loss-of-function G298S missense mutation on a background of a common H558R polymorphism in SCN5A (69).…”
Section: Visceral Painmentioning
confidence: 99%
“…Strege et al [24] suggested that a mechanosensitive Na + channel current is present in human intestinal ICC and appears to play a role in the control of intestinal motor function. Also in human jejunum, each ICC-MY generates spontaneous pacemaker activity that actively propagates through the ICC network, and the pacemaker activity was dependent on inositol-1,4,5-triphosphate receptor-operated stores and mitochondrial function [25] .…”
Section: Kim Bj Et Al Trpm7 and Interstitial Cells Of Cajalmentioning
confidence: 99%
“…33,34 Therefore, ICC determine the frequency of contractions. Additionally, ICC act as amplifiers of neuronal signals, 35,36 as mechanosensors, 37 and to set the smooth muscle membrane potential gradient. 38 A decreased number of ICC or a disrupted ICC network is associated with pathologic conditions such as slow transit constipation, 39,40 diabetic gastroparesis, 41 and pseudo-obstruction.…”
mentioning
confidence: 99%